Spatiotemporal characterization of the dynamic changes in the intestinal microbiota of Taihe Silky Fowl - Wentao Li; Haoneng Guo; Youping Wu; Yizhen Wang; Zeqing Lu (Animal Microbiome)
Abstract Background The aim of this study was to elucidate the dynamic characteristics of the Taihe Silky Fowl (TSF) intestinal microbiota systematically and predict their biological functions from hatching to market through large-scale sampling and 16S rRNA gene sequencing of a total of 288 samples taken at 8 timepoints from 3 intestinal regions to provide a theoretical basis for optimizing the intestinal microbiota to promote growth performance and intestinal health through artificial interventions on the basis of different growth ages and intestinal regions. Results The alpha and beta diversity of the intestinal microbiota changed significantly with age in different intestinal regions. In terms of alpha diversity, the ACE index and Shannon index followed the order cecum > rectum > duodenum, while the Simpson index followed the order rectum and duodenum > cecum. The PCoA plots revealed significant differences in beta diversity at different ages and in intestinal regions. The core phyla (top 5) in the TSF microbiota were Firmicutes, Bacteroidetes, Proteobacteria, Actinobacteria, and Cyanobacteria. The core genera (top 10) were Lactobacillus, Bacillus, Escherichia-Shigella, Alistipes, norank_o__Clostridia_UCG-014, Bacteroides, Faecalibacterium, norank_f__Ruminococcaceae, Enterococcus and Streptococcus. Additionally, the degree centrality of the cecal microbiota rapidly increased from hatching to 1 week of age, then rapidly decreased from 1 to 2 weeks of age, where it remained relatively stable until 21 weeks of age, whereas the betweenness centrality exhibited the opposite trend; the closeness centrality decreased continuously with age. The functions of the cecal microbiota varied at different ages, and the central functions were nucleic acid metabolism and protein synthesis at 0 weeks of age and carbohydrate metabolism and quorum sensing at 9 weeks of age. Conclusions In conclusion, the diversity, structure, composition, community relationships and functions of the intestinal microbiota in Taihe Silky Fowl dynamically changed with age in different intestinal regions.